ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - Wicaksono, Maheranto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyze the financial performance of companies on stock returns. Financial performance is represented by variables Return on assests ratio (ROA), Return on Equity (ROE), Current Ratio (CR), Debt To Total Assets (DTA), Net Profit Margin (NPM) and Earning Per Share (EPS). This type of research is an explanatory research (explanation). Total sample of 50 companies with 200 entries in the manufacturing sector companies listed on the Indonesia Stock Exchange. The method of analysis used in this study is multiple regression method. The results showed that the Return on Assests Ratio (ROA), Return on Equity (ROE), Current Ratio (CR), Debt To Total Assets (DTA), Net Profit Margin (NPM) and Earning Per Share (EPS) simultaneously affect the stock returns. Partial test shows that the variable Return on Assests Ratio (ROA), Return on Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) significant influence, while the variable Debt To Total Assets (DTA) and Current Ratio is not significant effect on stock returns. Of the variables mentioned above, Return on Equity is the dominant variable striving to stock return. Keywords: Financial Performance: Return on Assests Ratio (ROA), Return On Equity (ROE), Current Ratio (CR), Debt To Total Asset (DTA), Net Profit Margin (NPM), Earning Per Share (EPS) and Return stock